Cash holding and firm value in the presence of managerial optimism - Ashfaq Habib; Muhammad Ishaq Bhatti; Muhammad Asif Khan; Zafar Azam (Journal of Risk and Financial Management, 2021)
Cash holding is important for Chinese manufacturing firms coping with the increasing costs of financing and tough economic conditions. This study examines the impact of cash holding on the firm value of Chinese manufacturing businesses. We found evidence that a non-linear relationship exists between cash holding and firm value in these companies. The study reveals that a higher level of cash holding in financially constrained firms negatively affects the firm value, while unconstrained firms with a less cash holding level have a better firm value. Finally, this research is enriched by implementing the novel measure of managerial optimism. Revealed is the interactive role of cash holding and optimism and how they affect firm value. The study concludes that managerial optimism influences a firm's cash holding decisions, and this is more costly for unconstrained firms.
Keywords: 330; cash holding; financial constraint; firm value; managerial optimism